Carotid arteries in the dog: Structure and histophysiology - Orsi, Antonio M. [UNESP] (2006)
Light microscopy analysis of the mural structure of the common carotid artery, internal carotid artery and external carotid artery in mongrel dog revealed variability in the middle values of vascular diameter and thickness of the intimal plus medial coats and adventitial coat. The vascular diameter did not differ between the internal carotid artery and external carotid artery, but was significantly increased in the common carotid artery from which the other two arteries had origin. The increased thickness of the intimal plus medial coats of the common carotid artery revealed the constant mechanical adjustment of the arterial wall and local shearing stress that occurred among the arterial coats. The adventitial coat of the internal carotid artery was significantly thicker than those of the common carotid and external carotid arteries, with no significant difference noted between the latter arteries. These histomorphometric results were related to the qualitative observations regarding the mural structure of the three arteries analyzed, especially regarding to the increased thickness and structural complexity of the adventitial coat of the internal carotid artery. Perhaps it acted as an external protective sheath of the vascular wall during its long course until the carotid channel. © 2006 Sociedad Chilena de Anatomía.